Low Overhead Localized Routing in Mobile Ad Hoc Networks - Sumet Prabhavat; Worrawat Narongkhachavana; Thananop Thongthavorn; Chanakan Phankaew (My University, 2019)
Mobile Opportunistic Networks (OppNets) are infrastructure-less networks consisting of wireless mobile nodes and have been a focus of research for years. OppNets can be scaled up to support rapid growth of wireless devices and technologies, especially smartphones and tablets. Mobile Ad Hoc Networks (MANETs), one of OppNets technologies, have a high potential to be used for facilitating an extension for the Internet and a backup communication platform in disaster situation. However, a connection disruption due to node mobility and unreliable wireless links is possible to trigger a flooding operation of route repair process. This results in transmission delay and packet loss. The flooding of routing packets is an expensive operation cost in MANETs which affects network reliability and wastes limited resources such as network bandwidth and node energy. These are obstacles to practical implementation of MANETs in real-world environment. In this paper, we propose Low Overhead Localized Flooding (LOLF), an efficient overhead reduction routing extension based on Query Localization (QL) routing protocol. The purpose of this work is to control the propagation of routing packets in the route discovery and route repair mechanisms while incurring only a small increase in the size of control information in the packet. Simulation results from extensive experiments show that our proposed method can reduce overall routing overhead, energy consumption, and end-to-end delay without sacrificing the packet delivery ratio compared to existing protocols.
Keywords: Opportunistic and Delay-Tolerant Networks